2002
DOI: 10.1034/j.1600-0420.2002.800307.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of trabeculectomy in terms of intraocular pressure

Abstract: ABSTRACT. Purpose: To evaluate the outcome, long-term results and contributing prognostic factors of trabeculectomy in terms of intraocular pressure (IOP) and to compare the results in primary open-angle glaucoma (POAG) and exfoliation glaucoma (EG).Methods: This study involved retrospective evaluation of 138 consecutive patients (138 eyes) with either POAG or EG. All patients had undergone primary trabeculectomy performed by the same surgeon between November 1994 and August 1996. Only one eye per patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
3
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 17 publications
(23 reference statements)
8
73
3
7
Order By: Relevance
“…The previous study conducted in 1999, which found similar IOP-lowering effect in 30 eyes with PXG and 30 eyes with POAG during a follow-up period of 2 years reported the similar finding with present study [16]. However, the finding from studies published in 2002 and 2013 reported that complete success rates were significantly better in the POAG group than in the PXG group [12,17]. There were no a clear reasons why this discrepancy was happens.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The previous study conducted in 1999, which found similar IOP-lowering effect in 30 eyes with PXG and 30 eyes with POAG during a follow-up period of 2 years reported the similar finding with present study [16]. However, the finding from studies published in 2002 and 2013 reported that complete success rates were significantly better in the POAG group than in the PXG group [12,17]. There were no a clear reasons why this discrepancy was happens.…”
Section: Discussioncontrasting
confidence: 57%
“…In comparison with two different studies which utilize similar criteria with the present study, this amount of overall success rate in the present study is better [9,10]. However in comparison to three studies with success rates of 88%, 85% and 82%, the current result is lower [11][12][13]. The Trabeculectomy failure found in this study was 8 (11.6%).…”
Section: Discussioncontrasting
confidence: 47%
“…[20][21][22][23] Studies on Asian patients in South East Asia have also reported a lower success rate of trabeculectomy than the success rate reported on Caucasian populations in the western literature. 10,11,16 However, the survival of trabeculectomy improved with use of intraoperative antimetabolite as adjuvant, and the more liberal use of intraoperative antimetabolites was advocated in the Asian population. 11,12 Comparisons of survival of trabeculectomy performed in different populations were limited by the different clinical settings in various countries, such as surgical techniques, length of follow-up, and criteria for success.…”
Section: Discussionmentioning
confidence: 99%
“…From the studies conducted on overseas Asians with POAG, the success rate of trabeculectomy without use of antimetabolite appears to be lower than the success rate in Caucasian. 10,11,16 Wong et al reported a 3-year success rate of only 36% for trabeculectomy in Asians with POAG, but the rate was higher if antimetabolite was used and approached the rate observed in Caucasians reported in the western studies. 12,[16][17][18][19][20] However, comparison of glaucoma surgical management in Asian and Caucasian populations is difficult because of the different surgical techniques, ophthalmic practice and medical care environments, and glaucoma managements in different countries.…”
Section: Introductionmentioning
confidence: 97%
“…The mean reduction in IOP from 32.2 mm Hg (median ¼ 30.5; SD ¼ 11.4) in the preoperative period to 17.8 mm Hg (median ¼ 17.0; SD ¼ 5.8) at a year follow-up compares with report from other previous studies. 4,[17][18][19] There was no significant difference between the 5-FU and the non-5-FU groups at a year follow-up in term of their mean IOP (P ¼ 0.6). The survival curve between the two groups also failed to demonstrate any added advantage to the use of antimetabolites.…”
Section: Discussionmentioning
confidence: 99%